Exiting the crisis. - Corsetti, G; Devereux, M; Guiso, L; Hassler, J; Saint-Paul, G; Sinn, H; Sturm, J; Vives, X (CESifo Group Munich, 2010)
This edition of the Report on the European Economy by the European Economic Advisory Group at CESifo (EEAG), the ninth in the series, dissects the most salient aspects of the financial crisis that swept the world and, in particular, explores what needs to be done to nurture the incipient recovery. While the resolute action taken by the leaders of the affected countries has prevented the patient from dying, a number of chronic ailments still need to be addressed, posing new challenges for economists and policymakers. This is no time for complacency.